2021
DOI: 10.1177/0300060520987396
|View full text |Cite
|
Sign up to set email alerts
|

The iron chelator deferoxamine decreases myeloma cell survival

Abstract: Objective This study evaluated serum ferritin (SF) levels and investigated their relationships with various clinical markers in patients with multiple myeloma (MM). Furthermore, the effects and molecular mechanism of deferoxamine (DFO) in myeloma cells were studied. Methods Clinical data from 84 patients with MM were collected to evaluate SF content and its relationship with several important clinical parameters. MM1S and MM1R myeloma cells were chosen to investigate the effects of iron and DFO on cell surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Some studies have proposed ferritin as a negative prognostic factor in MM, as increased levels were shown to correlate with stage III disease and higher values of B2M, IL-6 and LDH expression [14]. These data are consistent with our results, where we showed an increase in mean ferritin values from MGUS to MM conditions and a significant rise of B2M in the HF group of MM patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some studies have proposed ferritin as a negative prognostic factor in MM, as increased levels were shown to correlate with stage III disease and higher values of B2M, IL-6 and LDH expression [14]. These data are consistent with our results, where we showed an increase in mean ferritin values from MGUS to MM conditions and a significant rise of B2M in the HF group of MM patients.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we identified ferritin as a potential new target for MM treatment, laying the groundwork for future combinatory studies that should include iron chelation as a backbone to enhance immunomodulatory agents or mAbs. Some preclinical evidence already supports this point [7,14,19,20]. Finally, further evidence is needed to fully validate ferritin as a new prognostic factor for MM, and to determine its role as a new potential target to improve patient outcome.…”
Section: Discussionmentioning
confidence: 97%
“…During ischemic stroke, the expression of interleukin-6 (IL-6) in cells increases hepcidin through the JAK/ STAT3 pathway (Cojocaru et al, 2009), which causes FPN1 degradation, resulting in reduced iron release and thus intensified iron accumulation in cells (Cojocaru et al, 2009;Zhou et al, 2017). Therefore, the rational application of iron metabolism inhibitors, such as deferoxamine and iron chelators, to reduce the iron content in the brain after an ischemic stroke can reduce neuronal death and promote the recovery of NVU function after ischemic stroke (Jones et al, 2020;Roemhild et al, 2021;Yang et al, 2021). In 2017, Tuo et al revealed the relationship between Tau and ferroptosis and the role of ferroptosis in CIRI using the MCAO mouse model (Tuo et al, 2017).…”
Section: Figurementioning
confidence: 99%